(untitled) (Studia theodisca, 2021)
In the light of the profound changes that have affected both the political scenario and the political role and forms of engagement of literature over the past thirty years, Monika Maron’s novel Munin oder Chaos im Kopf (2018) seems particularly topical. If analysed through Hannah Arendt’s remarks on the nature of politics and Zygmunt Bauman’s thoughts on our “besieged” society, the narrator’s shocking experience can be seen as both the consequence and the reflection of a failure of our democratic systems, as well as of our traditional idea of politics itself.